2007
DOI: 10.1007/s00428-007-0412-9
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression profiling of formalin-fixed paraffin-embedded tumor samples: a comparison to snap-frozen material using oligonucleotide microarrays

Abstract: Oligonucleotide microarrays are widely used to investigate gene expression in a large-scale approach. A major limitation is the dependency on frozen material to obtain high-quality ribonucleic acid because most clinical specimens are formalin-fixed and paraffin-embedded (FFPE). The ability to analyze these samples using microarrays would enlarge the investigable sample stocks manifold. We conducted a comparison of snap-frozen and FFPE tissues investigating two malignomas. Gene expression profiles were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…Whereas RT -PCR interrogation of archival FFPET has proven to be a reliable tool and is widely used (Cronin et al, 2004), this approach is unsuitable for large scale discovery-based investigation owing to the limited number of genes that can be assayed in one experiment. RNA from freshly prepared FFPET may be minimally degraded (von Ahlfen et al, 2007) and their transcript profiles correlate very well with those from paired unfixed FT (Lee et al, 2005a;Scicchitano et al, 2006;Frank et al, 2007), but these samples lack the requisite clinical follow-up data for correlation with expression data.…”
mentioning
confidence: 99%
“…Whereas RT -PCR interrogation of archival FFPET has proven to be a reliable tool and is widely used (Cronin et al, 2004), this approach is unsuitable for large scale discovery-based investigation owing to the limited number of genes that can be assayed in one experiment. RNA from freshly prepared FFPET may be minimally degraded (von Ahlfen et al, 2007) and their transcript profiles correlate very well with those from paired unfixed FT (Lee et al, 2005a;Scicchitano et al, 2006;Frank et al, 2007), but these samples lack the requisite clinical follow-up data for correlation with expression data.…”
mentioning
confidence: 99%
“…Bibikova et al 29 and Frank et al 30 assessed the reproducibility of FFPE samples profiled with oligonucleotide arrays and found high concordance between replicate samples. Likewise, high correlations (r !…”
Section: Discussionmentioning
confidence: 99%
“…These advances include newer formalin-fixed paraffin-embedded tissue extraction protocols, cDNA-mediated annealing, selection, extension and ligation, the addition of random hexamer priming to oligo(dT) priming and newly developed array platforms with redesigned probes. [30][31][32][33][34]57,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Although sensitivity is low, high specificity and positive predictive value suggest that transcript detection is reliable from formalin-fixed paraffin-embedded tissue. 33 Although RNA isolation techniques from formalin-fixed paraffin-embedded tissues have improved, problems remain, largely because of the greater fragmented nature of RNA in formalin-fixed paraffin-embedded tissue.…”
Section: Discussionmentioning
confidence: 99%
“…33 Although RNA isolation techniques from formalin-fixed paraffin-embedded tissues have improved, problems remain, largely because of the greater fragmented nature of RNA in formalin-fixed paraffin-embedded tissue. 30,32,75,78 Magnitudes of differential expression are often higher in formalin-fixed paraffin-embedded tissue than in fresh frozen samples, because of the increased background noise; this increases the odds of false-positive results. 30,83 Despite these concerns, several studies have shown comparable biological information between genome-wide microarray analysis from matched fresh frozen and formalin-fixed paraffin-embedded tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation